Perancangan Konsep Desain Antarmuka Website Sdit Attaqwa Ambulu Sebagai Media Informasi Terpadu - Salsabila Nurrahma Nadiya; Pungky Febi Arifianto; Sri Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
This research explores the process of designing a user interface for the SDIT Attaqwa Ambulu website, aimed at serving as a centralized digital information platform. It addresses the school’s communica-tion challenges, which still rely on traditional media like brochures and inconsistent social media management. A qualitative descriptive method was employed, using interviews, observations, and ques-tionnaires for data collection. The findings indicate a strong demand from parents and the local community for a digital platform that de-livers clear, organized, and visually appealing content. The design development process included audience identification, needs analy-sis, formulation of visual and verbal concepts, creation of wireframes, user flow mapping, and high-fidelity design work. Vali-dation involved guidance from academic advisors, feedback from stakeholders, and critique from a UI/UX practitioner—focusing on layout consistency, color readability, and the use of functional ele-ments such as buttons and cards. The final output is a user-friendly website design that combines a modern aesthetic with Islamic visual identity, aiming to enhance the school’s branding and improve pub-lic access to essential information.